O ToyArt como mecanismo de valorização da fauna e flora da UFAM - Silva, Raylane Natividade da (Brasil, 2025)
ToyArt, contemporary art products focused on collecting and decoration, serves as a mechanism of expression that blends art and design. These products have the power to generate critiques and reflections, evoking emotions and affections related to childhood, which creates a lasting connection into adulthood. This work aims to explore ToyArt as an environmental awareness tool through the creation of dolls inspired by the local fauna and flora of the Federal University of Amazonas, the largest green area in an urban setting in the country. The adopted method, exploratory in nature, compiles previous studies to provide a better understanding of the topic, using a qualitative approach. For this, online questionnaires were applied to university visitors, gathering their opinions on the research proposal. As a result, four characters inspired by animals and plants from the university's green area were created, along with the three-dimensional materialization of a doll that represents the presented proposal.